Low Rise Apartment Design - Irfan Aldyanto; Husna Izzati; Andiyan Andiyan (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2022)
Kota Baru Parahyangan is a rapidly growing independent city with many facilities including Residential, Commercial, Recreational, and Public Areas. In addition, Kota Baru Parahyangan has an integrated and directed area development plan called the Town Center, which will be developed into a